Direct demonstration of tubular fluid flow sensing by macula densa cells - Sipos, Arnold (American Physiological Society, 2010)
Macula densa (MD) cells in the cortical thick ascending limb (cTAL) detect variations in tubular fluid composition and transmit signals to the afferent arteriole (AA) that control glomerular filtration rate [tubuloglomerular feedback (TGF)]. Increases in tubular salt at the MD that normally parallel elevations in tubular fluid flow rate are well accepted as the trigger of TGF. The present study aimed to test whether MD cells can detect variations in tubular fluid flow rate per se. Calcium imaging of the in vitro microperfused isolated JGA-glomerulus complex dissected from mice was performed using fluo-4 and fluorescence microscopy. Increasing cTAL flow from 2 to 20 nl/min (80 mM [NaCl]) rapidly produced significant elevations in cytosolic Ca(2+) concentration ([Ca(2+)](i)) in AA smooth muscle cells [evidenced by changes in fluo-4 intensity (F); F/F(0) = 1.45 ± 0.11] and AA vasoconstriction. Complete removal of the cTAL around the MD plaque and application of laminar flow through a perfusion pipette directly to the MD apical surface essentially produced the same results even when low (10 mM) or zero NaCl solutions were used. Acetylated α-tubulin immunohistochemistry identified the presence of primary cilia in mouse MD cells. Under no flow conditions, bending MD cilia directly with a micropipette rapidly caused significant [Ca(2+)](i) elevations in AA smooth muscle cells (fluo-4 F/F(0): 1.60 ± 0.12) and vasoconstriction. P2 receptor blockade with suramin significantly reduced the flow-induced TGF, whereas scavenging superoxide with tempol did not. In conclusion, MD cells are equipped with a tubular flow-sensing mechanism that may contribute to MD cell function and TGF.